Review of the Transitional Pain Service as a method of postoperative opioid weaning and a service aimed at minimizing the risk of chronic post-surgical pain - Mikhaeil, John; Ayoo, Kennedy; Clarke, Hance; Wąsowicz, Marcin; Huang, Alexander (Anestezjologia Intensywna Terapia, 2020)
Opioid use and prescribing have become a subject of increasing focus and scrutiny. The ongoing “opioid epidemic” in North America has further increased interest in this area. In patients presenting for surgery, the prescribing of opioids during and following admission to hospital is commonplace and has been identified as a potential contributor to the growing opioid problem in North America. This review aims to present the timeline of the “opioid epidemic” as well as to introduce the concept of a “Transitional Pain Service”. The Transitional Pain Service is a multidisciplinary service originating at Toronto General Hospital that employs a multi-faceted approach to monitoring opioid use after discharge from surgery, and aims to safely wean patients from opioids while maintaining effective pain management. This approach and its results will be discussed in this review.